Acute fluid shifts influence the assessment of serum vitamin D status in critically ill patients - Krishnan, Anand (BioMed Central, 2010)
INTRODUCTION: Recent reports have highlighted the prevalence of vitamin D deficiency and suggested an association with excess mortality in critically ill patients. Serum vitamin D concentrations in these studies were measured following resuscitation. It is unclear whether aggressive fluid resuscitation independently influences serum vitamin D. METHODS: Nineteen patients undergoing cardiopulmonary bypass were studied. Serum 25(OH)D(3), 1α,25(OH)(2)D(3), parathyroid hormone, C-reactive protein (CRP), and ionised calcium were measured at five defined timepoints: T1 - baseline, T2 - 5 minutes after onset of cardiopulmonary bypass (CPB) (time of maximal fluid effect), T3 - on return to the intensive care unit, T4 - 24 hrs after surgery and T5 - 5 days after surgery. Linear mixed models were used to compare measures at T2-T5 with baseline measures. RESULTS: Acute fluid loading resulted in a 35% reduction in 25(OH)D(3 )(59 ± 16 to 38 ± 14 nmol/L, P < 0.0001) and a 45% reduction in 1α,25(OH)(2)D(3 )(99 ± 40 to 54 ± 22 pmol/L P < 0.0001) and i(Ca) (P < 0.01), with elevation in parathyroid hormone (P < 0.0001). Serum 25(OH)D(3 )returned to baseline only at T5 while 1α,25(OH)(2)D(3 )demonstrated an overshoot above baseline at T5 (P < 0.0001). There was a delayed rise in CRP at T4 and T5; this was not associated with a reduction in vitamin D levels at these time points. CONCLUSIONS: Hemodilution significantly lowers serum 25(OH)D(3 )and 1α,25(OH)(2)D(3), which may take up to 24 hours to resolve. Moreover, delayed overshoot of 1α,25(OH)(2)D(3 )needs consideration. We urge caution in interpreting serum vitamin D in critically ill patients in the context of major resuscitation, and would advocate repeating the measurement once the effects of the resuscitation have abated.